Freedom of Contract in Carriage Law - Marek BIALKOWSKI (Communications of International Proceedings, 2021)
Freedom of contract, in carriage law in particular, is an extremely important determinant of the correct and civil-law compliant execution of contracts. Its significance for the parties of a contractual relation cannot be overestimated. Regardless of how it is perceived, it has its source in the civil law provisions but it is also strongly rooted in the regulation of norms of the Constitution of the Republic of Poland. A contract for carriage in this context, although it has an established place in the provisions of the civil code and although it is a type of a nominate contract, in fact it contains a number of distinct features included in completely separate non-code regulations, thanks to which it constitutes its fundamental regulatory core. Such an approach to its functioning clearly and unambiguously allows recourse, in the event of interpretation doubts, to provisions and interpretation that refer to civil law and civil proceedings, thus creating a certain system for using its provisions.
Keywords: Freedom of Contract; Carriage Law; Civil Law; Contractual Relations.